Keberlanjutan Transportasi di Kota Surabaya Melalui Pengembangan Kawasan Berbasis TOD (Transit Oriented Development) - Ketut Dewi Martha Erli Handayani; Putu Gde Ariastita (Diponegoro University, 2014)
Development plan of monorail and tramway in Surabaya City aimed to encourage the movement based transit. TOD (Transit Oriented Development) is model for integration of transportation and land use in order to encourage the transit ridership. The result of study in worldwide show the success of TOD application in increasing the usage of transit mode by developing policies on land uses around station/terminal. Therefore, it needs to adopt TOD in transit area of Surabaya City to achieve the sustainable transportation. This study conclude criteria of TOD that can be applied in transit area of Surabaya City are mixed land uses, high intensity of activities around station/terminal, integrated design of circulation and road network, and pedestrians/cyclists friendly design.Development plan of monorail and tramway in Surabaya City aimed to encourage the movement based transit. TOD (Transit Oriented Development) is model for integration of transportation and land use in order to encourage the transit ridership. The result of study in worldwide show the success of TOD application in increasing the usage of transit mode by developing policies on land uses around station/terminal. Therefore, it needs to adopt TOD in transit area of Surabaya City to achieve the sustainable transportation. This study conclude criteria of TOD that can be applied in transit area of Surabaya City are mixed land uses, high intensity of activities around station/terminal, integrated design of circulation and road network, and pedestrians/cyclists friendly design.